Perancangan Sisttem Pendukung Proses Perkuliahan Di Universitas Atma Jaya Makassar - Lidyawati Liaupati (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2016)
This research focuses on designing lectures support system in the form of Learning Management System (LMS) at Atma Jaya Makassar University. The use of information system at Atma Jaya Makassar University is limited to support academic administration activities and still not support learning activities. This is due to the lack of information system provided by Atma Jaya Makassar University that can support the lectures at Atma Jaya Makassar University, especially self-directed learning based on Student Centered Learning (SCL). This research aims to design a system that is able to assist lecturer to provide learning materials, as well as support evaluation of students’s self directed learning. System development method used in this research is spiral method. The results of this research are indicate that the system is able to support self-directed learning of the learning process in UAJM as well as 80% of students found the system easy to understand and use.